Reduction of ileocolic intussusception with hydrostatic enema under ultrasound guidance in pediatric patients: Case report - Matos Rojas, Irma Aracelly (2023)
Ileocolic intussusception is a pediatric emergency with initial non-surgical treatment. Ultrasound-guided hydrostatic reduction in pediatric patients is a widely used initial treatment method in the world; however, its use is not widespread in our environment. We present 4 cases of patients with ileocolic intussusception treated by ultrasound-guided hydrostatic reduction in the Instituto Nacional de Salud del Niño – San Borja (INSNSB), with therapeutic reduction and without complications.